2011
DOI: 10.3109/10799893.2011.563311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thapsigargin on Ca2+fluxes and viability in human prostate cancer cells

Abstract: Effect of the carcinogen thapsigargin on human prostate cancer cells is unclear. This study examined if thapsigargin altered basal [Ca²⁺](i) levels in suspended PC3 human prostate cancer cells by using fura-2 as a Ca²⁺-sensitive fluorescent probe. Thapsigargin at concentrations between 10 nM and 10 µM increased [Ca²⁺](i) in a concentration-dependent fashion. The Ca²⁺ signal was reduced partly by removing extracellular Ca²⁺ indicating that Ca²⁺ entry and release both contributed to the [Ca²⁺](i) rise. This Ca²⁺… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Taken together, the time course data presented here suggest that the overall inhibitory effect of thapsigargin and tunicamycin was due to glioblastoma cell death. These results are similar to those from other studies on several types of human cancer that also demonstrated that thapsigargin (18)(19)(20)(21) and tunicamycin (22)(23)(24) promoted tumor cell death.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Taken together, the time course data presented here suggest that the overall inhibitory effect of thapsigargin and tunicamycin was due to glioblastoma cell death. These results are similar to those from other studies on several types of human cancer that also demonstrated that thapsigargin (18)(19)(20)(21) and tunicamycin (22)(23)(24) promoted tumor cell death.…”
Section: Resultssupporting
confidence: 93%
“…To this end, in this study, we demonstrate that two endoplasmic reticulum stress inducers, thapsigargin and tunicamycin, promote glioblastoma cell death. Our findings are consistent with those from previous studies on several human cancers that also showed that thapsigargin (prostate, breast, leukemia, and melanoma) (18)(19)(20)30,32) and tunicamycin (neuroblastoma and melanoma) induced tumor cell death (24,33).…”
Section: Discussionsupporting
confidence: 94%
“…Huang et al identified a [Ca 2+ ] i -dependent apoptotic mechanism in PC3 human prostate cancer cells exposed to thapsigargin (1–10 µM). Here, the rise in [Ca 2+ ] i was attributed to both Ca 2+ -influx from extracellular environment and depletion of ER stores [128]. Combination treatment with TRAIL (70 and 35 ng/mL) and thapsigargin (0.3 and 0.6 μM) induced apoptosis and inhibited migration, invasion, and adhesion of ESCC cell lines (esophageal squamous cell carcinoma), demonstrating that this combination induces both apoptosis and inhibits metastasis [129].…”
Section: Targeting Calcium Signaling For Anti-cancer Therapymentioning
confidence: 99%
“…In the present paper, to further identify the role of Pink1 in neuronal protections against oxidative stress and apoptosis, we investigated the expression alternations of Pink1 under oxidative conditions and whether altered Pink1 expression affected neuron survival. Thapsigargin is a specific irreversible inhibitor of endoplasmic reticulum (ER) calcium-ATPase, which leads ectopic calcium entry and causes oxidative stress and apoptosis [ 14 , 15 ]. We found that thapsigargin could lead to dramatic neuronal apoptosis by promoting oxidative stress in neurons and causes lipid peroxidations and protein oxidative carbonylations.…”
Section: Introductionmentioning
confidence: 99%